Velocity. - Martiniere, Stephan, ....- (Culver City : Designstudio, 2011)
Following his previous books, Quantum Dreams and Quantumscapes, Velocity is a stunning new visionary collection of sci-fi book cover paintings, commercial and film art, video game designs, and never before-seen artwork from the fantastic imagination of acclaimed artist Stephan Martiniere.